Q&A for matriculation physics - Poh, Liong Yong; Leong, Kok Ong (Oxford Fajar Sdn Bhd, 2015)
Q&A for Matriculation Physics Semester 1 Second Edition Updated is a comprehensive question and answer book for students studying Physics in local Matriculation colleges. Written by experienced authors and based on the Matriculation Physics SF016 syllabus, this book provides effective revision and exam-oriented self-assessment for students to prepare for examinations. It exposes students to examination-type questions, guides them in answering such questions, and provides further questions for practice.The level of English is kept simple to assist students' learning of the subject. Each chapter begins with a section entitled Formulae and Notes which contains brief notes and/or formulae to refresh the student's memory. This is followed by three major sections: Subjective Questions, Objective Questions, and Challenge Questions. In Subjective Questions, each individual question is followed immediately by its answer. This section is aimed at guiding students in answering structured questions, while Challenge Questions provide students with further practice in answering this type of question. Two sets of Model Examination Papers with model answers are given at the end of the book. In addition, Answer Guide to Objective Questions at the end of the book contains guidance for answering most of the objective questions in the book.